“Only a Life Lived for Others Is Worth Living”: Redox Signaling by Oxygenated Phospholipids in Cell Fate Decisions - Tyurina, Yulia Y. (Antioxid Redox Signal, 2018)
Significance: Oxygenated polyunsaturated lipids are known to play multi-functional roles as essential signals coordinating metabolism and physiology. Among them are well-studied eicosanoids and docosanoids that are generated via phospholipase A(2) hydrolysis of membrane phospholipids and subsequent oxygenation of free polyunsaturated fatty acids (PUFA) by cyclooxygenases and lipoxygenases. Recent Advances: There is an emerging understanding that oxygenated PUFA-phospholipids also represent a rich signaling language with yet-to-be-deciphered details of the execution machinery—oxygenating enzymes, regulators, and receptors. Both free and esterified oxygenated PUFA signals are generated in cells, and their cross-talk and inter-conversion through the de-acylation/re-acylation reactions is not sufficiently explored. Critical Issues: Here, we review recent data related to oxygenated phospholipids as important damage signals that trigger programmed cell death pathways to eliminate irreparably injured cells and preserve the health of multicellular environments. We discuss the mechanisms underlying the trans-membrane redistribution and generation of oxygenated cardiolipins in mitochondria by cytochrome c as pro-apoptotic signals. We also consider the role of oxygenated phosphatidylethanolamines as proximate pro-ferroptotic signals. Future Directions: We highlight the importance of sequential processes of phospholipid oxygenation and signaling in disease contexts as opportunities to use their regulatory mechanisms for the identification of new therapeutic targets.